A theory of formal conceptual definitions: developing theory‐building measurement instruments - Wacker, John G. (Journal of Operations Management, 2004)
AbstractThis study develops the need for formal conceptual definitions (sometimes called nominal definitions) and how to develop better measurement instruments for theory‐building. It develops the underlying theory for ‘good’ formal conceptual definitions by defining terms, demonstrating that formal conceptual definitions are needed for all theory‐building empirical research, explains how and why ‘good’ formal conceptual definitions are used to develop properties and their measures, and last, it logically explains that good formal conceptual definitions are necessary conditions for construct validity (content validity, criterion validity, convergent validity, and discriminant validity) while statistical tests are sufficient conditions for validity. This theory development explains why formal conceptual definitions are necessary before any traditional statistical empirical validity tests are performed. This study suggests that any statistical validity tests are not meaningful if the concept is not formally defined.In short, the theory of formal conceptual definitions provides a structure to develop ‘good’ measures of the formal theory that leads to ‘good’ empirical theory‐building.